Corporate disclosure and disseminaton of human resources investment information / Zubaidah Zainal Abidin and Dennis Taylor - Zainal Abidin, Zubaidah; Dennis, Taylor (Faculty of Accountancy & Accounting Research Institute (ARI), 2002)
This study seeks to bring three theoretical perspectives to bear on uncovering motives for the disclosure of human resource (HR) investment related information in corporate annual reports. Institutional, agency and resource-dependency theories of organizational behaviour are used to support arguments about attitudes of finance managers and HR managers to such disclosure decisions. Drawing from listed companies in Malaysia, a field survey was conducted amongst the finance and HR managers of those companies. Malaysia is particularly suitable for this study because corporations have relatively high levels of investment in human resources (mainly training and development expenditure) due to federal government subsidies. The survey results reveal contrasts in the significance of relationships between institutional, agency and resource dependency-driven variables and the extent of corporate disclosure ofHR information. Multiple-theory modelling implications for studies of corporate disclosures, as well as practical implications of the findings for the voluntary corporate reporting of HR information, are discussed.